Understanding the effect of Mn2+ on Yb3+/Er3+ upconversion and obtaining a maximum upconversion fluorescence enhancement in inert-core/active-shell/inert-shell structures. Issue 86 (5th September 2016) - Huang, Zhangyu; Gao, Huiping; Mao, Yanli
Abstract : NaYF4 @NaYF4 :Er 3+ /Yb 3+ /Mn 2+ @NaYF4 (C/Sd /S) nanoparticles were synthesized which show an obvious efficiency enhancement of red upconversion emission. Abstract : In this study, the energy transfer (ET) mechanism among Yb 3+ /Er 3+ /Mn 2+ has been revealed by download conversion (DC) and upconversion (UC) transients and steady-state fluorescence spectra. Moreover, the novel structure, inert-core/active-shell/inert-shell cubic NaYF4 @NaYF4 :Er 3+ /Yb 3+ /Mn 2+ @NaYF4, has been synthesized via a convenient hydrothermal method. With the excitation of a 980 nm laser diode, bright single-red upconversion (UC) fluorescence is observed, which shows the longest UC lifetime and highest efficiency compared with the other structures of NaYF4 :Er 3+ /Yb 3+ /Mn 2+, NaYF4 :Er 3+ /Yb 3+ /Mn 2+ @NaYF4, and NaYF4 @NaYF4 :Er 3+ /Yb 3+ /Mn 2+ . The inert-core/active-shell/inert-shell nanocubes are homogeneous with an ultra-small (sub-20 nm) size, which is suitable for distribution and elimination in biological tissue. Our results indicate that the Mn 2+ doping of δ-doped structures is an effective method to significantly improve UC single-red light, which shows great potential application in vivo bioimaging.